Distributed-order calculus: An operator-theoretic interpretation - Kochubei, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Within the Bochner-Phillips functional calculus and Hirsch functional calculus, we describe the operators of distributed-order differentiation and integration as functions of the classical operators of differentiation and integration, respectively.